MOMEN GERHANA MATAHARI MENYAMBUT ROMADHON 1447 H (2026 M) SEBAGAI STANDAR SUDUT MES = OO UNTUK MENYUSUN DATABASE 1 SYAWAL - Ruby, Tiryono; Assyfa Mahatir Princess (Bajang Institute, 2025)
Differences in determining the 1st of Ramadan often become disputes between groups or organizations among Muslims, with differences of opinion about the 1st of Ramadan also causing differences regarding the Eid al-Fitr holiday in each group or organization. With the MES (Moon, Earth, Sunset) angle measurement method, the degree of the crescent moon to the earth can be measured, so it can be known when the 1st of Ramadan or Eid al-Fitr holiday is. From this method, it can be known when the moment of the solar eclipse shrinks MES = 0o (ijtimak / conjunction). Compiling the database of 1 Shawwal against the Gregorian calendar